Tribal womens involvement with pig farming in Bangladesh: an evidence of Moulvibazar district (SAARC Journal of Agriculture, 2018)
The study examined the profitability and factors affecting farm income from pig farming in Moulvibazar district of Bangladesh. A multistage sampling technique was followed to select 70tribal women entrepreneurs involved with pig farming. Primary data were collected through structured questionnaire and analyzed using descriptive statistics, independent sample t-test, benefit-cost analysis, and linear regression model. Average age of pig entrepreneurs was 39.47 years which indicates that they are young and agile. About 71% of Garo entrepreneurs had experience for pig farming. The cost and return analysis showed that in one year, the gross margin was Tk. 56743.70, while the benefit-cost ratio (BCR) was 1.19 indicating that the enterprise is profitable. Regression analysis revealed that three variables namely farm size, age of the respondent and experience of pig farming are significant factors affecting farm income. Thus, it was recommended that tribal women should be encouraged to practice pig farming to overcome their low income and unemployment situation.SAARC J. Agri., 16(1): 115-127 (2018)